Resource selection of apex raptors: implications for siting energy development in sagebrush and prairie ecosystems. Issue 8 (26th August 2020) - Squires, John R.; Olson, Lucretia E.; Wallace, Zachary P.; Oakleaf, Robert J.; Kennedy, Patricia L.
Abstract: There is an urgent need to understand ecological responses of avian species to the rapidly expanding human footprint of conventional and renewable energy development in sagebrush and prairie ecosystems. The ferruginous hawk ( Buteo regalis ) and golden eagle ( Aquila chrysaetos ) are two sympatric raptors of conservation concern that occupy and flourish in the most intact sagebrush steppe region remaining in North America. To understand these species' use of habitat relative to energy development, we built resource selection functions using a spatially representative sample of occupied nesting territories collected in 2010–2011 and remotely sensed environmental variables across an extensive study area (186, 693 km 2 ). We used the resulting predicted resource selection maps to evaluate spatial overlap between the nesting habitats of these sympatric raptor species, as well as overlap of predicted habitat with potential development of oil/gas and wind energy resources. Remotely sensed variables were very effective in modeling patterns of nest‐site selection based on fivefold cross‐validation (>0.93 Spearman‐rank correlation) and validation with an independent dataset of historical nests collected from 2000 to 2009. Topographic roughness and intermediate levels of spring precipitation were the strongest drivers of differences in habitat use between ferruginous hawks and golden eagles. We did not detect a strong signal of avoidance of energy infrastructure by either species at current levels of development and both nested closer than expected to gravel/dirt roads associated with oil and gas infrastructure. However, extensive overlap of nesting habitat more selected by ferruginous hawks and golden eagles with areas of actual and potential energy development suggests both species are at risk from future habitat fragmentation. Given that 80% of nests are> 1 km from oil/gas wells, we believe the density of energy‐related disturbance present during our study was insufficient to drive patterns of resource selection for ferruginous hawks when considered at broad spatial scales. However, it was beyond the scope of our study to predict long‐term, population‐level responses. We suggest rigorous monitoring of long‐term trends in occupancy, productivity, and distribution is warranted for populations of ferruginous hawk and golden eagle in sagebrush and prairie ecosystems exposed to increased energy development.